O narracyjności reportażu radiowego - Sygizman, Kinga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The author takes up the question of the narrativity of the artistic radio message that is radio documentary. It looks at documenatry from the perspective of psychological research on storytelling. Hence it considers the radio documentary as a large-scale narration composed of smaller aural forms, constituting small narrations. The author examines numerous levels of the in-depth news report, lexical, prosodic and also phonic features. It also shows how the theory of radio documentary connects to narrative identity.